Synthesis, characterization and evaluation of antibacterial activity of copper(II)-curcumin complex against staphylococcus aureus - Le Dang Khoa,; Hoang Minh Hao, (Journal of Technical Education Science, 2021)
Curcumin, a phytochemical from turmeric, and its derivatives have been extensively investigated from both chemical and biological strategies. However, the main problem encountered while using curcumin in clinical trials is its poor solubility and rapid degradation, resulting in its low levels in tissues, thus decreasing the medicinal effect of curcumin. To overcome these problems several synthetic approaches have been carried out to prepare new derivatives possessing better properties. Curcumin as a β-diketone ligand can act as chelating ligands toward a variety of metals to form stable complexes. Some studies showed that a metal-curcumin complex displayed potential medicinal activities. In this work, a copper(II)-curcumin complex was synthesized in a two-step procedure: (i) curcumin was separated from commercial turmeric powder using chromatography techniques and (ii) the copper(II) chloride (1 eq.) and pure curcumin (2 eq.) were mixed together in ethanol. The mixture was stirred at 60 oC for 3 hours to afford a stoichiometric copper(II)-curcumin complex. The curcumin ligand and its copper(II) complex were characterized by UV-Vis, IR, NMR spectroscopic methods, from which it was found that copper atoms are coordinated through keto-enol groups of two curcumin molecules. The ground state spectral features of the copper(II)-curcumin complex were consistent with that of the 1:2 copper(II)-curcumin complex. The antibacterial activities of curcumin ligand and its complex were evaluated against Staphylococcus aureus (ATCC 6538) using a well diffusion method on nutrient agar. The results showed that the inhibitory activity was not observed for free curcumin at any concentrations while the copper(II)-curcumin complex exhibited the inhibition zones (mm) of 7.8, 11.6 and 14.9 at various concentrations (mg/mL) of 1.0, 5.0 and 15.0, respectively.